2006
DOI: 10.1108/09578230610676587
|View full text |Cite
|
Sign up to set email alerts
|

New principals in Africa: preparation, induction and practice

Abstract: PurposeThis paper aims to examine the challenges facing new principals in Africa.Design/methodology/approachBased on recent research and literature, the paper analyses the experience of principals and proposes an induction model for principalship in Africa.FindingsSchool principals in Africa face a daunting challenge. They often work in poorly equipped buildings with inadequately trained staff. There is rarely any formal leadership training and principals are appointed on the basis of their teaching record rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
117
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(158 citation statements)
references
References 11 publications
6
117
0
4
Order By: Relevance
“…There has never been a formal entry qualification into the principalship in South Africa, except for a general teaching qualification. This is not only the case for South Africa, but for all other African countries and beyond as noted by Bush and Oduro (2006). These authors indicate that in Africa, principals are often appointed on the basis of a successful record as teachers.…”
Section: Training For Principalshipmentioning
confidence: 89%
“…There has never been a formal entry qualification into the principalship in South Africa, except for a general teaching qualification. This is not only the case for South Africa, but for all other African countries and beyond as noted by Bush and Oduro (2006). These authors indicate that in Africa, principals are often appointed on the basis of a successful record as teachers.…”
Section: Training For Principalshipmentioning
confidence: 89%
“…Researchers such as Grissom and Harrington (2010) and Leithwood et al (2004) have demonstrated that training the school leadership team is fundamental to improving learning and transferring knowledge (Leithwood et al, 2004;Grissom and Harrington, 2010;Swaffield et al, 2013). However, to date, little has been done to improve the school leadership teams in Africa, particularly in West Africa (Bush and Oduro, 2006;Bush et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Third, a second hand search of reports issued by aid agencies and Non-Governmental Organizations (NGOs) working in Malawi in the education sector generated several reports on the work of these organizations but nothing specific on the preparation of headteachers except for three failed attempts by the Department for International Development (DFID), the World Bank and the African Development Bank. Bush and Oduro (2006) state what resonates with many scholars who have conducted research on the preparation of headteachers in Africa. "Throughout Africa", they write "there is no formal requirement for principals to be trained as school managers.…”
Section: Review Of Literaturementioning
confidence: 75%